Leadership and self-deception getting out of the box - The Arbinger Institute (San Francisco Berrett-Koehler Publishers, 2010)
Through a story everyone can relate to about a man facing challenges on the job and in his family, the authors expose the fascinating ways that we can blind ourselves to our true motivations and unwittingly sabotage the effectiveness of our own efforts to achieve success and increase happiness.
Includes index.
Keywords: Leadership